Buying America back - Greenberg, Jonathan (Council Oak Books, 1992)
An immensely valuable resource for policymakers, community activists and everyone concerned with building a more humane future, this collection of 45 essays brims with important proposals for social and economic change. Jonathan Becker of Critical Mass, a public interest group, sets forth a national plan for achieving greater reliance on renewable energy sources and greater energy efficiency. Adm. Gene La Roeque advocates closing overseas military bases, slashing the war budget and weaning the U.S. from its role of world policeman. Ethan Nadelman, a Princeton professor of politics, argues for controlled legalization of drugs. Other contributors call for a national health insurance system, judicial reform, comprehensive day care, elimination of wasteful CIA spending, a value-added environmental impact fee to curb production of polluting products, and linkage of housing assistance to human services policies with the aim of preventing homelessness. Robert Heilbroner, Hazel Henderson, Richard Barnet and Kirkpatrick Sale are among the contributors to this inspiring volume, which ranges from discussions on campaign financing to education to the AIDS crisis. Greenberg is a business journalist; Kistler heads a New York investment fund.